2017
DOI: 10.22158/ra.v3n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Responsibility for Food Safety

Abstract: Nowadays, food safety and quality have a key role in maintaining the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Literature data indicated that there are many gaps in food safety knowledge and often poor hygiene practice among final consumers (Sanlier, 2009;Langiano et al, 2012;Janjic et al, 2017;Moreb et al, 2017), especially for some consumer groups, such as young adults aged from 18 to 29, males and people with higher education (Medeiros et al, 2001(Medeiros et al, , 2004Byrd-Bredbenner et al, 2007, 2008. In general, young adults are not considered to be at risk in terms of food poisonings, but they might be also susceptible to foodborne disease due to their risky eating behavior, such as eating raw milk, cheese prepared of raw milk, raw fish, raw shellfish, undercooked eggs, undercooked red meat, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data indicated that there are many gaps in food safety knowledge and often poor hygiene practice among final consumers (Sanlier, 2009;Langiano et al, 2012;Janjic et al, 2017;Moreb et al, 2017), especially for some consumer groups, such as young adults aged from 18 to 29, males and people with higher education (Medeiros et al, 2001(Medeiros et al, , 2004Byrd-Bredbenner et al, 2007, 2008. In general, young adults are not considered to be at risk in terms of food poisonings, but they might be also susceptible to foodborne disease due to their risky eating behavior, such as eating raw milk, cheese prepared of raw milk, raw fish, raw shellfish, undercooked eggs, undercooked red meat, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective protection from the public health risks associated with contaminated foods can be attained through collaborative effort [ 76 ]. That is, the regulators and managers, especially, must commit to their mandate and be resolved to protecting consumers from food-related public health and safety risks [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pesticide related symptoms can be associated to this fact. But surprisingly, they are aware of the fact that carrot treated with pesticides is not good for consumption, so they don't consume treated carrot to certain extent 26 .…”
Section: Discussionmentioning
confidence: 99%